Epigenetic remodelling and dysregulation of DLGAP4 is linked with early-onset cerebellar ataxia - Minocherhomji, Sheroy (Hum Mol Genet, 2014)
Genome instability, epigenetic remodelling and structural chromosomal rearrangements are hallmarks of cancer. However, the coordinated epigenetic effects of constitutional chromosomal rearrangements that disrupt genes associated with congenital neurodevelopmental diseases are poorly understood. To understand the genetic–epigenetic interplay at breakpoints of chromosomal translocations disrupting CG-rich loci, we quantified epigenetic modifications at DLGAP4 (SAPAP4), a key post-synaptic density 95 (PSD95) associated gene, truncated by the chromosome translocation t(8;20)(p12;q11.23), co-segregating with cerebellar ataxia in a five-generation family. We report significant epigenetic remodelling of the DLGAP4 locus triggered by the t(8;20)(p12;q11.23) translocation and leading to dysregulation of DLGAP4 expression in affected carriers. Disruption of DLGAP4 results in monoallelic hypermethylation of the truncated DLGAP4 promoter CpG island. This induced hypermethylation is maintained in somatic cells of carriers across several generations in a t(8;20) dependent-manner however, is erased in the germ cells of the translocation carriers. Subsequently, chromatin remodelling of the locus-perturbed monoallelic expression of DLGAP4 mRNAs and non-coding RNAs in haploid cells having the translocation. Our results provide new mechanistic insight into the way a balanced chromosomal rearrangement associated with a neurodevelopmental disorder perturbs allele-specific epigenetic mechanisms at breakpoints leading to the deregulation of the truncated locus.